Inflammation, Aging and Hematopoiesis: A Complex Relationship - Pavlos Bousounis (Cells, 2021)
All vertebrate blood cells descend from multipotent hematopoietic stem cells (HSCs), whose activity and differentiation depend on a complex and incompletely understood relationship with inflammatory signals. Although homeostatic levels of inflammatory signaling play an intricate role in HSC maintenance, activation, proliferation, and differentiation, acute or chronic exposure to inflammation can have deleterious effects on HSC function and self-renewal capacity, and bias their differentiation program. Increased levels of inflammatory signaling are observed during aging, affecting HSCs either directly or indirectly via the bone marrow niche and contributing to their loss of self-renewal capacity, diminished overall functionality, and myeloid differentiation skewing. These changes can have significant pathological consequences. Here, we provide an overview of the current literature on the complex interplay between HSCs and inflammatory signaling, and how this relationship contributes to age-related phenotypes. Understanding the mechanisms and outcomes of this interaction during different life stages will have significant implications in the modulation and restoration of the hematopoietic system in human disease, recovery from cancer and chemotherapeutic treatments, stem cell transplantation, and aging.